1992
DOI: 10.1016/0168-9525(92)90213-n
|View full text |Cite
|
Sign up to set email alerts
|

Splicing with inverted order of exons occurs proximal to large introns

Abstract: Following our studies which showed that the a and [ exons of the chicken c-ets-1 gene are not conserved in the human homologue, we succeeded in identifying a novel human c-ets-1 transcript in which the normal order of exons is scrambled. By PCR and RNase protection assays, we demonstrated that while the order of exons is different from that in genomic DNA, splicing of these exons in aberrant order occurs in pairs and at the same conserved consensus splice sites used in the normally spliced transcript. The scra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The serendipitous discovery of circular transcripts generated from the gene deleted in colorectal cancer ( DCC ), which encodes a cell surface receptor for the guidance cue Netrin-1, demonstrated that circRNAs can actually originate from transcribed genes (Nigro et al, 1991). In the following years, circRNA isoforms derived from several other loci were found in cells, including from the ETS-1, Dystrophin and Cytochrome P-450 2C18 genes (Cocquerelle et al, 1992; Saad et al, 1992; Bailleul, 1996; Zaphiropoulos, 1997). Initially, these circRNAs were thought to be potentially pathogenic byproducts of aberrant splicing or ‘transcriptional/splicing noise’ and did not receive much attention.…”
Section: Introductionmentioning
confidence: 99%
“…The serendipitous discovery of circular transcripts generated from the gene deleted in colorectal cancer ( DCC ), which encodes a cell surface receptor for the guidance cue Netrin-1, demonstrated that circRNAs can actually originate from transcribed genes (Nigro et al, 1991). In the following years, circRNA isoforms derived from several other loci were found in cells, including from the ETS-1, Dystrophin and Cytochrome P-450 2C18 genes (Cocquerelle et al, 1992; Saad et al, 1992; Bailleul, 1996; Zaphiropoulos, 1997). Initially, these circRNAs were thought to be potentially pathogenic byproducts of aberrant splicing or ‘transcriptional/splicing noise’ and did not receive much attention.…”
Section: Introductionmentioning
confidence: 99%